Utilization of Senjoyo Springs in the Development of Tegalwanto Village in Tenggaran District, Semarang Regency - Baharui Gulo; Dyah Palupiningtyas (Pusat Riset dan Inovasi Nasional, 2024)
The development strategy derived from the SWOT analysis of Senjoyo Springs highlights the utilization of its internal strengths, especially the potential of natural conditions, to improve the quality and attractiveness of tourist attractions. Exploiting open markets and product diversification is an effective strategy for optimizing external opportunities. To overcome internal weaknesses, such as limited capital, as well as anticipate external threats, such as weather changes, actions are needed to strengthen the position of Senjoyo Springs in the natural tourism market. The contribution of Senjoyo Springs Nature Tourism to local community income is around 30.97%, showing a positive impact on the local economy, in line with previous findings regarding the economic benefits of nature tourism. Development recommendations include more intensive environmental management efforts, aggressive promotion, and close collaboration between the government, tourism managers and the community. Focusing on human resource management and increasing community knowledge regarding sustainable practices through training and education is critical. In the long term, regular monitoring of strategy implementation and its impact is essential to maintain the sustainability of Senjoyo Springs as a tourist attraction that provides sustainable economic, social and environmental benefits.